Macroeconomic factors that affecting the movement of economic growth in Malaysia / Nor Azureen Ahmad Zakaria - Ahmad Zakaria, Nor Azureen (Faculty of Business and Management, 2019)
The issue of the of economic growth is at the critical stages especially in Malaysia which need to be overcome before it may cause the similar problem on 1997 and 2008 which is financial crisis were occurred during that time and cause Malaysia’s economy drastically dropped into negative percent. So that, the fluctuation of economic growth needs to be evaluated. This study is using the time series data which investigate only one country which is Malaysia and many periods of time from 1988 to 2018. This research finding also have been studied to achieve the objective where to examine the significant relationship between economic growth and the independent variables in Malaysia from 1988-2018. The Multiple Linear Regression (MLR) model had been used in this study to see the relationship between the economic growth with all the macroeconomic factors which are export, inflation rate, foreign direct investment and interest rate. The final findings for this study show that, foreign direct investment is the most significant variable that can affect the movement of economic growth in Malaysia followed by export and interest rate. In addition, there is shows a positive relationship for foreign direct investment towards the economic growth in Malaysia. This means that the higher the foreign direct investment, the higher the economic growth in Malaysia. In contrast, this study was found that export and interest rate are negative relationship on economic growth in Malaysia. However, inflation rate has negative but insignificant relationship with economic growth in Malaysia. All the data from this study are collected from Economic Global Data in annually basis from year 1988 until 2018.